Changes in emergency department utilisation in Germany before and during different phases of the COVID-19 pandemic, using data from a national surveillance system up to June 2021 - Schranz, Madlen; Boender, T. Sonia; Greiner, Timo; Kocher, Theresa; Wagner, Birte; Greiner, Felix; Bienzeisler, Jonas; Diercke, Michaela; Grabenhenrich, Linus; Brokmann, Jörg; Mach, Carsten; Wehler, Markus; et al. (BMC Public Health, 2023)
Background: During the COVID-19 pandemic and associated public health and social measures, decreasing patient numbers have been described in various healthcare settings in Germany, including emergency care. This could be explained by changes in disease burden, e.g. due to contact restrictions, but could also be a result of changes in utilisation behaviour of the population. To better understand those dynamics, we analysed routine data from emergency departments to quantify changes in consultation numbers, age distribution, disease acuity and day and hour of the day during different phases of the COVID-19 pandemic. Methods: We used interrupted time series analyses to estimate relative changes for consultation numbers of 20 emergency departments spread throughout Germany. For the pandemic period (16-03-2020 – 13-06-2021) four different phases of the COVID-19 pandemic were defined as interruption points, the pre-pandemic period (06-03-2017 – 09-03-2020) was used as the reference. Results: The most pronounced decreases were visible in the first and second wave of the pandemic, with changes of − 30.0% (95%CI: − 32.2%; − 27.7%) and − 25.7% (95%CI: − 27.4%; − 23.9%) for overall consultations, respectively. The decrease was even stronger for the age group of 0–19 years, with − 39.4% in the first and − 35.0% in the second wave. Regarding acuity levels, consultations assessed as urgent, standard, and non-urgent showed the largest decrease, while the most severe cases showed the smallest decrease. Conclusions: The number of emergency department consultations decreased rapidly during the COVID-19 pandemic, without extensive variation in the distribution of patient characteristics. Smallest changes were observed for the most severe consultations and older age groups, which is especially reassuring regarding concerns of possible long-term complications due to patients avoiding urgent emergency care during the pandemic.
CRIS-Team Scopus Importer:2025-02-03
Keywords: COVID-19 pandemic; Emergency department; Interrupted time series analyses; Public health and social measures; Routine data; Syndromic surveillance